Encyclopedia of chemical technology - Kirk, Raymond E. (Raymond Eller), 1890-1957; Grayson, Martin; Eckroth, David (Wiley, 1978)
Alphabetical arrangement of entries that reflect current topics of interest to scientists, chemists, and engineers, e.g., health, safety, toxicology, and new materials. Comprehensive coverage. Each entry consists of lengthy signed article, with illustrations and bibliography